Manajemen Peserta Didik Dalam Perkembangan Karakter Inklusif - Khawaiji, Imron; Wibowo, Adi; Daimah (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to comprehensively describe the management of the character education strengthening program at the elementary school level. The method used is a case study with a qualitative approach, located at SD Mutiara Ibu Purworejo. Data collection was conducted through observation, interviews, and documentation. Data analysis went through three stages: data condensation, data presentation, and conclusion drawing. The results showed several important findings. First, the planning of student management in inclusive character development includes initial observation, coordination meetings, program planning, implementation, monitoring, and evaluation. Second, the principal acts as the main person in charge with the support of the school development team and program coordinators. Third, program implementation is carried out through four main strategies: integration into learning, value cultivation, role modeling, and collaboration with parents. Fourth, program supervision is carried out directly and continuously. Fifth, program evaluation includes evaluation planning, implementation, data processing, and follow-up meetings for program improvement. Thus, the management of the character strengthening program at SD Mutiara Ibu Purworejo runs systematically and involves all school components as well as parents